Robotic system for top to bottom MRgFUS therapy of multiple cancer types - Antoniou, Anastasia; Giannakou, Marinos; Evripidou, Nikolas; Stratis, Stylianos; Pichardo, Samuel; Damianou, Christakis A. (My University, 2022)
Background: A robotic system for Magnetic Resonance guided Focussed Ultrasound (MRgFUS) therapy of tumours in the breast, bone, thyroid, and abdomen was developed. Methods: A special C-shaped structure was designed to be attached to the table of conventional magnetic resonance imaging (MRI) systems carrying 4 computer-controlled motion stages dedicated to positioning a 2.75 MHz spherically focussed transducer relative to a patient placed in the supine position. The developed system was evaluated for its MRI compatibility and heating abilities in agar-based phantoms and freshly excised tissue. Results: Compatibility of the system with a clinical high-field MRI scanner was demonstrated. FUS heating in the phantom was successfully monitored by magnetic resonance thermometry without any evidence of magnetically induced phenomena. Cigar-shaped discrete lesions and well-defined areas of overlapping lesions were inflicted in excised tissue by robotic movement along grid patterns. Conclusions: The developed MRgFUS robotic system was proven safe and efficient by ex-vivo feasibility studies.
Keywords: MRI compatible; Top to bottom; Multipurpose; Robotic system; Ex vivo tissue ablation; Focussed ultrasound